2008
DOI: 10.1097/ogx.0b013e318186a9c7
|View full text |Cite
|
Sign up to set email alerts
|

Postterm Pregnancy: How Can We Improve Outcomes?

Abstract: After completion of this article, the reader should be able to recall the increasing risks of poor outcomes associated with prolonged pregnancy, demonstrate knowledge regarding gestational dating and use of cervical ripening agents in their care of pregnant women, and use evidence-based information when counseling their term patients regarding postterm pregnancy management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 88 publications
(103 reference statements)
1
39
0
3
Order By: Relevance
“…Detailed information on exactly which biometric parameters were used to calculate gestational age was not recorded in the Birth Register, but as all the parameters seem to be affected by fetal sex, they can cause a systematic error, when used for ultrasound dating. [32][33][34][35] It is still unclear whether using crown-to-rump-length measurement in the first trimester for dating of pregnancies would decrease this systematic error, as some studies have reported a sex difference in fetal crown-rump length whereas another has not. 32,36 Though ultrasound for assessment of gestational length in general is better than LMP and should be the preferred method for pregnancy dating, it is important to be aware of its shortcomings.…”
Section: Discussionmentioning
confidence: 97%
“…Detailed information on exactly which biometric parameters were used to calculate gestational age was not recorded in the Birth Register, but as all the parameters seem to be affected by fetal sex, they can cause a systematic error, when used for ultrasound dating. [32][33][34][35] It is still unclear whether using crown-to-rump-length measurement in the first trimester for dating of pregnancies would decrease this systematic error, as some studies have reported a sex difference in fetal crown-rump length whereas another has not. 32,36 Though ultrasound for assessment of gestational length in general is better than LMP and should be the preferred method for pregnancy dating, it is important to be aware of its shortcomings.…”
Section: Discussionmentioning
confidence: 97%
“…Selon les articles et les définitions utilisées, dans la catégo-rie des grossesses à terme dépassé, les décès foetaux repré-sentent 1,6 pour 1000 à 3,5 pour 1000 naissances [5,8,[20][21][22] et l'incidence de la mortalité périnatale est de 2,9 à 4,2 pour 1000 naissances à 42 +0 SA et au-delà [4,19,20,22] (NP2).…”
Section: Au Niveau Internationalunclassified
“…Alors que l'incidence de la mortalité foetale dans les grossesses à terme dépassé dans les pays anglo-saxons (Canada et États-Unis) se situe autour de 3,5 pour 1000 naissances, celle des pays scandinaves est bien inférieure et se situe entre 1,6 et 2,3 ‰ [5,8,[20][21][22]. Cette différence s'observe aussi pour l'incidence de la mortalité périnatale dans le cadre des grossesses à terme dépassé : en Amérique-du-Nord, cette incidence est de 3,3 pour 1000 naissances, alors qu'en Scandinavie elle est estimée autour de 2,9 pour 1000 [4,20,26] (NP2).…”
Section: Variations Dans Le Temps Et Entre Les Paysunclassified
“…Post-term pregnancy, defined as gestational age > 42 weeks from the first day of the last menstrual period, or the estimated date of delivery (EDD)+14 days [2], has been associated with various adverse maternal and perinatal outcomes [5,13]. Mandujano et al report that the risk of fetal death associated with remaining undelivered increases after term for low-risk pregnancies and after 36 weeks for highrisk pregnancies [18].…”
Section: Introductionmentioning
confidence: 99%